Solve the differential equation $\left( {{e}^{x}}+1 \right)ydy+\left( y+1 \right)dx=0$.
Answer
Verified
503.4k+ views
Hint: Use a variable separable method to solve the given differential equation. Integrate with respect to ‘dx’ and ‘dy’ to both sides and simplify it to get the solution of the given differential equation.
Complete step-by-step answer:
We have
$\left( {{e}^{x}}+1 \right)ydy+\left( y+1 \right)dx=0.............\left( i \right)$
Dividing the whole equation by dx, we get,
$\left( {{e}^{x}}+1 \right)y\dfrac{dy}{dx}+\left( y+1 \right)\dfrac{dx}{dx}=0$
Or
$\left( {{e}^{x}}+1 \right)y\dfrac{dy}{dx}+\left( y+1 \right)=0..........(ii)$
Now, as we know, we have three types of differential equations i.e., separable, linear and homogeneous.
Now, by observation, we get that if we divide equation (ii), by ‘y’ then we can separate variables ‘x’ and ‘y’ easily. Hence, the given differential equation belongs to a separable type.
So, on dividing equation (ii), we get
$\left( {{e}^{x}}+1 \right)\dfrac{y}{y}\dfrac{dy}{dx}+\left( \dfrac{y+1}{y} \right)=0$
Or
$\left( {{e}^{x}}+1 \right)\dfrac{dy}{dx}+\dfrac{y+1}{y}=0$
Now transferring $\dfrac{y+1}{y}$ to other side, we get
$\left( {{e}^{x}}+1 \right)\dfrac{dy}{dx}=-\dfrac{\left( y+1 \right)}{y}..........(iii)$
Now, we can transfer functions of variable ‘x’ to one side and functions of variable ‘y’ to another side to integrate the equation with respect to ‘dx’ and ‘dy’.
So, equation (iii) can be written as
$\left( \dfrac{y}{y+1} \right)dy=\dfrac{-1}{{{e}^{x}}+1}dx$
Now, we observe that variable are easily separated, so we can integrate them with respect to
‘x’ and ‘y’ hence, we get
$\int{\dfrac{y}{y+1}dy=-\int{\dfrac{1}{{{e}^{x}}+1}dx............(iv)}}$
Let ${{I}_{1}}=\int{\dfrac{y}{y+1}dy}$ and ${{I}_{2}}=\int{\dfrac{1}{{{e}^{x}}+1}dx}$
Let us solve both the integration individually.
So, we have ${{I}_{1}}$ as,
${{I}_{1}}=\int{\dfrac{y}{y+1}dy}$
Adding and subtracting ‘1’ in numerator, we get,
${{I}_{1}}=\int{\dfrac{\left( y+1 \right)-1}{\left( y+1 \right)}dy}$
Now, we can separate (y+1) as
\[{{I}_{1}}=\int{\dfrac{y+1}{y+1}dy}-\int{\dfrac{1}{y+1}dy}\]
Or
\[{{I}_{1}}=\int{1dy}-\int{\dfrac{1}{y+1}dy}\]
As we know,
$\begin{align}
& \int{\dfrac{1}{x}dx}=\ln x \\
& \int{{{x}^{n}}dx=\dfrac{{{x}^{n+1}}}{n+1}} \\
\end{align}$
So, ${{I}_{1}}$ can be simplified as,
${{I}_{1}}=\int{{{y}^{0}}dy-\ln \left( y+1 \right)+{{C}_{1}}}$
\[{{I}_{1}}=y-\ln \left( y+1 \right)+{{C}_{1}}............\left( v \right)\]
Now, we have ${{I}_{2}}$ as
${{I}_{2}}=\int{\dfrac{1}{{{e}^{x}}+1}dx}$
Multiplying by ${{e}^{-x}}$ in numerator and denominator we get,
${{I}_{2}}=\int{\dfrac{{{e}^{-x}}}{{{e}^{x}}.{{e}^{-x}}+{{e}^{-x}}}dx}$
As we have property of surds as, ${{m}^{a}}.{{m}^{b}}={{m}^{a+b}}$
So, we can write ${{I}_{2}}$ as
${{I}_{2}}=\int{\dfrac{{{e}^{-x}}}{1+{{e}^{-x}}}dx}..............\left( vi \right)$
Let us suppose $1+{{e}^{-x}}=t$.
Differentiating both sides w.r.t. x, we get
$-{{e}^{-x}}=\dfrac{dt}{dx}$
Where $\dfrac{d}{dx}{{e}^{x}}={{e}^{x}}$, so, we have
${{e}^{-x}}dx=-dt$
Substituting these values in equation (vi), we get
${{I}_{2}}=\int{\dfrac{-dt}{t}=-\int{\dfrac{dt}{t}}}$
Now, we know that $\int{\dfrac{1}{t}dt=\ln t}$ hence,
${{I}_{2}}=-\ln t+{{C}_{2}}$
Since, we have value of t as \[1+{{e}^{-x}}\], hence ${{I}_{2}}$ in terms of x can be given as
${{I}_{2}}=-\ln \left( 1+{{e}^{-x}} \right)+{{C}_{2}}.............\left( vii \right)$
Hence, from equation (iv), (v) and (vii) we get,
$\begin{align}
& y-\ln \left( y+1 \right)+{{C}_{1}}=-\left( -\ln \left( 1+{{e}^{-x}} \right)+{{C}_{2}} \right) \\
& y-\ln \left( y+1 \right)+{{C}_{1}}=\ln \left( 1+{{e}^{-x}} \right)-{{C}_{2}} \\
& y-\ln \left( y+1 \right)=\ln \left( 1+{{e}^{-x}} \right)+{{C}_{3}} \\
\end{align}$
Where $-{{C}_{2}}-{{C}_{1}}={{C}_{3}}$
Let us replace ${{C}_{3}}$ by ‘ln C’, so we get above equation as
$y-\ln \left( y+1 \right)=\ln \left( 1+{{e}^{-x}} \right)+\ln C........\left( viii \right)$
Now, we know that \[\text{ln }a+\ln b=\ln ab\], so, equation (viii) can be given as
$y=\ln \left( y+1 \right)+\ln \left( C\left( 1+{{e}^{-x}} \right) \right)$
$y=\ln \left( C\left( y+1 \right)\left( 1+{{e}^{-x}} \right) \right)$
As we know that if ${{a}^{x}}=N$ then $x={{\log }_{a}}N$ or vice versa.
Hence, above equation can be written as
$C\left( y+1 \right)\left( 1+{{e}^{-x}} \right)={{e}^{y}}$
This is the required solution.
Note: One can go wrong if trying to solve the given differential equation by a homogenous method, as the given equation is not a homogeneous differential equation so we cannot apply this method to a given variable separable differential equation.
Observing the given differential equation as a variable separable equation is the key point of the question.
Complete step-by-step answer:
We have
$\left( {{e}^{x}}+1 \right)ydy+\left( y+1 \right)dx=0.............\left( i \right)$
Dividing the whole equation by dx, we get,
$\left( {{e}^{x}}+1 \right)y\dfrac{dy}{dx}+\left( y+1 \right)\dfrac{dx}{dx}=0$
Or
$\left( {{e}^{x}}+1 \right)y\dfrac{dy}{dx}+\left( y+1 \right)=0..........(ii)$
Now, as we know, we have three types of differential equations i.e., separable, linear and homogeneous.
Now, by observation, we get that if we divide equation (ii), by ‘y’ then we can separate variables ‘x’ and ‘y’ easily. Hence, the given differential equation belongs to a separable type.
So, on dividing equation (ii), we get
$\left( {{e}^{x}}+1 \right)\dfrac{y}{y}\dfrac{dy}{dx}+\left( \dfrac{y+1}{y} \right)=0$
Or
$\left( {{e}^{x}}+1 \right)\dfrac{dy}{dx}+\dfrac{y+1}{y}=0$
Now transferring $\dfrac{y+1}{y}$ to other side, we get
$\left( {{e}^{x}}+1 \right)\dfrac{dy}{dx}=-\dfrac{\left( y+1 \right)}{y}..........(iii)$
Now, we can transfer functions of variable ‘x’ to one side and functions of variable ‘y’ to another side to integrate the equation with respect to ‘dx’ and ‘dy’.
So, equation (iii) can be written as
$\left( \dfrac{y}{y+1} \right)dy=\dfrac{-1}{{{e}^{x}}+1}dx$
Now, we observe that variable are easily separated, so we can integrate them with respect to
‘x’ and ‘y’ hence, we get
$\int{\dfrac{y}{y+1}dy=-\int{\dfrac{1}{{{e}^{x}}+1}dx............(iv)}}$
Let ${{I}_{1}}=\int{\dfrac{y}{y+1}dy}$ and ${{I}_{2}}=\int{\dfrac{1}{{{e}^{x}}+1}dx}$
Let us solve both the integration individually.
So, we have ${{I}_{1}}$ as,
${{I}_{1}}=\int{\dfrac{y}{y+1}dy}$
Adding and subtracting ‘1’ in numerator, we get,
${{I}_{1}}=\int{\dfrac{\left( y+1 \right)-1}{\left( y+1 \right)}dy}$
Now, we can separate (y+1) as
\[{{I}_{1}}=\int{\dfrac{y+1}{y+1}dy}-\int{\dfrac{1}{y+1}dy}\]
Or
\[{{I}_{1}}=\int{1dy}-\int{\dfrac{1}{y+1}dy}\]
As we know,
$\begin{align}
& \int{\dfrac{1}{x}dx}=\ln x \\
& \int{{{x}^{n}}dx=\dfrac{{{x}^{n+1}}}{n+1}} \\
\end{align}$
So, ${{I}_{1}}$ can be simplified as,
${{I}_{1}}=\int{{{y}^{0}}dy-\ln \left( y+1 \right)+{{C}_{1}}}$
\[{{I}_{1}}=y-\ln \left( y+1 \right)+{{C}_{1}}............\left( v \right)\]
Now, we have ${{I}_{2}}$ as
${{I}_{2}}=\int{\dfrac{1}{{{e}^{x}}+1}dx}$
Multiplying by ${{e}^{-x}}$ in numerator and denominator we get,
${{I}_{2}}=\int{\dfrac{{{e}^{-x}}}{{{e}^{x}}.{{e}^{-x}}+{{e}^{-x}}}dx}$
As we have property of surds as, ${{m}^{a}}.{{m}^{b}}={{m}^{a+b}}$
So, we can write ${{I}_{2}}$ as
${{I}_{2}}=\int{\dfrac{{{e}^{-x}}}{1+{{e}^{-x}}}dx}..............\left( vi \right)$
Let us suppose $1+{{e}^{-x}}=t$.
Differentiating both sides w.r.t. x, we get
$-{{e}^{-x}}=\dfrac{dt}{dx}$
Where $\dfrac{d}{dx}{{e}^{x}}={{e}^{x}}$, so, we have
${{e}^{-x}}dx=-dt$
Substituting these values in equation (vi), we get
${{I}_{2}}=\int{\dfrac{-dt}{t}=-\int{\dfrac{dt}{t}}}$
Now, we know that $\int{\dfrac{1}{t}dt=\ln t}$ hence,
${{I}_{2}}=-\ln t+{{C}_{2}}$
Since, we have value of t as \[1+{{e}^{-x}}\], hence ${{I}_{2}}$ in terms of x can be given as
${{I}_{2}}=-\ln \left( 1+{{e}^{-x}} \right)+{{C}_{2}}.............\left( vii \right)$
Hence, from equation (iv), (v) and (vii) we get,
$\begin{align}
& y-\ln \left( y+1 \right)+{{C}_{1}}=-\left( -\ln \left( 1+{{e}^{-x}} \right)+{{C}_{2}} \right) \\
& y-\ln \left( y+1 \right)+{{C}_{1}}=\ln \left( 1+{{e}^{-x}} \right)-{{C}_{2}} \\
& y-\ln \left( y+1 \right)=\ln \left( 1+{{e}^{-x}} \right)+{{C}_{3}} \\
\end{align}$
Where $-{{C}_{2}}-{{C}_{1}}={{C}_{3}}$
Let us replace ${{C}_{3}}$ by ‘ln C’, so we get above equation as
$y-\ln \left( y+1 \right)=\ln \left( 1+{{e}^{-x}} \right)+\ln C........\left( viii \right)$
Now, we know that \[\text{ln }a+\ln b=\ln ab\], so, equation (viii) can be given as
$y=\ln \left( y+1 \right)+\ln \left( C\left( 1+{{e}^{-x}} \right) \right)$
$y=\ln \left( C\left( y+1 \right)\left( 1+{{e}^{-x}} \right) \right)$
As we know that if ${{a}^{x}}=N$ then $x={{\log }_{a}}N$ or vice versa.
Hence, above equation can be written as
$C\left( y+1 \right)\left( 1+{{e}^{-x}} \right)={{e}^{y}}$
This is the required solution.
Note: One can go wrong if trying to solve the given differential equation by a homogenous method, as the given equation is not a homogeneous differential equation so we cannot apply this method to a given variable separable differential equation.
Observing the given differential equation as a variable separable equation is the key point of the question.
Recently Updated Pages
Master Class 11 English: Engaging Questions & Answers for Success
Master Class 11 Computer Science: Engaging Questions & Answers for Success
Master Class 11 Maths: Engaging Questions & Answers for Success
Master Class 11 Social Science: Engaging Questions & Answers for Success
Master Class 11 Economics: Engaging Questions & Answers for Success
Master Class 11 Business Studies: Engaging Questions & Answers for Success
Trending doubts
10 examples of friction in our daily life
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE
State and prove Bernoullis theorem class 11 physics CBSE
Pigmented layer in the eye is called as a Cornea b class 11 biology CBSE
What problem did Carter face when he reached the mummy class 11 english CBSE